Introduction: Women and work from feminist perspectives - Lachover, Einat; Nagar-Ron, Sigal (Hagar: Studies in Society and Culture, 2014)
From Mary Wollstonecraft (1792/1978) to Virginia Woolf (1929/1974; 1938/1977) and Betty Friedan (1963) through bell hooks (2000) and Sylvia Walby (Walby, 1990), feminist theoreticians have repeatedly identified the role and importance of women’s work as a major element in understanding sexist social orders and in promoting social equality for women. This point of view is usually linked to the importance of work as the source of ownership over economic resources, such as food, property and capital. Other aspects of work have also been identified as crucial to women’s liberation: a sense of self-worth; a sense of purpose and accomplishment; the ability to contribute to society as a whole; experience with and control over social orders outside the home; and a sense of self-sufficiency. Hence, feminist theories have underlined the close connection between what work means for women within the culture and their economic status in the culture (Stewart, 1990). Intellectual analyses and research studies deriving from the various streams of feminism – liberal, radical, Marxist, socialist, and post-colonist – have analysed the meaning of women’s work in the context of reproducing the existing social and gender order, and of perpetuating male dominance (for a comprehensive discussion, see Ferguson & Hennessy, 2010).